Description of Favites monticularis sp. Nov. (Faviidae) off North Andaman Islands, India - T. Mondal (Journal of Threatened Taxa, 2013)
A new species Favites monticularis sp. nov. belonging to the family Faviidae is described from North Andaman Islands. Presence of monticules shaped structures distinguishthis species from the already known species of genus Favites. Key characters and morphological features of this new species and its affinity with other closely related species are described in this paper.